Nanoelectromechanical Chip (NELMEC) Combination of Nanoelectronics and Microfluidics to Diagnose Epithelial and Mesenchymal Circulating Tumor Cells from Leukocytes. Issue 7 (5th January 2016) - Hosseini, Seied Ali; Abdolahad, Mohammad; Zanganeh, Somayeh; Dahmardeh, Mahyar; Gharooni, Milad; Abiri, Hamed; Alikhani, Alireza; Mohajerzadeh, Shams; Mashinchian, Omid
Abstract : An integrated nano‐electromechanical chip (NELMEC) has been developed for the label‐free distinguishing of both epithelial and mesenchymal circulating tumor cells (ECTCs and MCTCs, respectively) from white blood cells (WBCs). This nanoelectronic microfluidic chip fabricated by silicon micromachining can trap large single cells (>12 µm) at the opening of the analysis microchannel arrays. The nature of the captured cells is detected using silicon nanograss (SiNG) electrodes patterned at the entrance of the channels. There is an observable difference between the membrane capacitance of the ECTCs and MCTCs and that of WBCs (measured using SiNG electrodes), which is the key indication for our diagnosis. The NELMEC chip not only solves the problem of the size overlap between CTCs and WBCs but also detects MCTCs without the need for any markers or tagging processes, which has been an important problem in previously reported CTC detection systems. The great conductivity of the gold‐coated SiNG nanocontacts as well as their safe penetration into the membrane of captured cells, facilitate a precise and direct signal extraction to distinguish the type of captured cell. The results achieved from epithelial (MCF‐7) and mesenchymal (MDA‐MB231) breast cancer cells circulated in unprocessed blood suggest the significant applications for these diagnostic abilities of NELMEC. Abstract : An integrated nano‐electromechanical chip (NELMEC) is developed for the label‐free diagnosis of both epithelial and mesenchymal circulating tumor cells. Large single cells (>12 µm) are trapped at the opening of the microchannels. Observable differences in membrane capacitance, as measured by silicon nanograss electrodes patterned at the entrance of the channels, forms the key indication factor in this diagnostic approach.